SMA-based self-centering eccentrically braced frame with vertical link member. (September 2022) - Garmeh, Vandad; Akbarpour, Abbas; Adibramezani, Mohammadreza; Hojat Kashani, Ata; Adibi, Mahdi
Abstract: This paper presents a comprehensive numerical investigation on a self-centering eccentrically braced frame (SEBF) with a vertical link member consisting of inner and outer link components. These components are respectively bolted to floor beam and Chevron braces using shape memory alloy bolts, which provide self-centering driving forces. When a lateral load is applied, the inner link component freely slides inside the outer one to shorten the length of the vertical link member to prevent additional forces and deformations in the floor beam and braces. The seismic input energy is dissipated through the superelastic deformations of the shape memory alloy bolts and the friction between the link components. To prove the efficiency of the proposed self-centering system, a comprehensive finite element analysis is carried out using Abaqus software. In this regard, first, the numerical modeling results are validated using the existing experimental studies in the literature. Then, the effect of key design parameters on the cyclic behavior of the proposed SEBF is investigated. The proposed self-centering system demonstrated stable hysteresis behavior with almost no residual drifts. The proposed system also offered moderate energy dissipation with equivalent viscous damping of up to 15%.